Good multiple sclerosis (MS) care and how to get there in Canada: Perspectives of Canadian healthcare providers working with persons with MS - Petrin, Julie; Marrie, Ruth Ann; Devonshire, Virginia; Jichici, Draga; Hrebicek, Olinka; Metz, Luanne M.; Morrow, Sarah A.; Oh, Jiwon; Smyth, Penelope; Donkers, Sarah J. (Frontiers in Neurology, 2023)
Objective: The literature that has examined healthcare access and needs of the multiple sclerosis (MS) population is limited. Currently, no research has engaged healthcare providers delivering services to this population to examine their perspectives on the provision of MS care in Canada. We aimed to summarize what good MS care should look like according to Canadian healthcare providers working with people with MS, and to identify the supports and resources required, within their care setting, to enable this standard of care. Methods: A qualitative descriptive approach was taken to analyze data from participants who responded to additional open-ended survey questions, within a larger “MS Models of Care Survey” targeting Canadian healthcare providers working with persons with MS. Results: Currently, a gap exists between what healthcare providers working with persons with MS believe MS care should encompass and what they are able to offer. Participants emphasized that their MS clinics are currently understaffed and patient-to-provider ratios are high, leaving very little time to address the array of healthcare concerns their patients present with. The healthcare providers overwhelmingly described that moving towards multidisciplinary team-based MS care that includes appropriate numbers of MS-trained neurologists, nurses, physiotherapists, occupational therapists, and mental health providers working within one location would be their prioritized approach to comprehensively managing MS care. This model of care enables all professionals to effectively coordinate care and use their time efficiently by only focusing on their area of expertise, all while meeting the needs of their patient in one setting, reducing wait-times and improving overall care. Conclusion: To meet the care needs of Canadians with MS, the healthcare system must consider standardizing and funding multidisciplinary team-based MS clinics, comparable to Stroke units, which continue to show favorable health outcomes after years of implementation.